The Use of Social Media for English Language Learning: An Exploratory Study of EFL University Students - Tubagus Zam Zam Al Arif (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
This study aims to examine the use of social media in English language learning by the students of English Study Program at Jambi University. This study applied an exploratory study to investigate the use of social media for English language learning. The researcher employed a survey and semi-structured interview in collecting the data. Sixty-seven students participated to answer the questionnaire and ten participants were interviewed, randomly selected from participants who answered the questionnaire. Basic statistical analysis was used to analyze quantitative data from the questionnaire, and the data from interviews were analyzed using phenomenological case analysis combined with coding thematically. The findings indicated that a range of social media especially Instagram and Facebook are used by the students. Consequently, the students spent more time in using social media for general purposes than English learning purposes. However, they showed positive attitudes towards the use of social media in English language learning. The students perceive that social media plays an important role to improve their English language skills. Furthermore, it promotes social media use and encourages students to use social media to improve their English language skills. In addition, the social media, which is mostly used in learning English by the university students of English Study Program at Jambi University, is Instagram, and they usually use the social media for learning English at home.